Risk behavior and access to HIV/AIDS prevention services in a community sample of homeless persons entering permanent supportive housing. Issue 5 (4th May 2017) - Wenzel, Suzanne L.; Rhoades, Harmony; Harris, Taylor; Winetrobe, Hailey; Rice, Eric; Henwood, Ben
ABSTRACT: Homeless persons suffer disproportionately high rates of HIV infection, and moving into permanent supportive housing (PSH) can provide a stable base from which to access needed prevention services. However, little is known about HIV risk or prevention behavior during this critical time of transition. The current study investigated STI and HIV risk and prevention behavior and recent use of prevention and treatment services (i.e., education, testing, medication) among homeless persons preparing to move into PSH. Data come from interviews with 421 homeless adults before they moved into PSH. Thirty-seven percent of the respondents were sexually active; of those, 75.7% reported unprotected sex. Nearly two-thirds (64%) reported past year HIV testing and 40% reported testing for another STI. Fewer than one-third (31%) of respondents reported receiving posttest counseling at their last HIV test. HIV seropositivity was self-reported by 10%. Among those persons who were HIV-positive, 57.1% reported less than 100% antiretroviral (ARV) adherence. Among HIV-negative respondents, less than 1% had been prescribed preexposure prophylaxis (PrEP). Less than half (46.4%) of the sample reported any HIV prevention education in the past year. This population of homeless adults about to move into PSH report high rates of HIV risk behavior, but low rates of HIV prevention education and very little PrEP utilization. Further, low rates of ARV adherence among HIV-positive respondents indicate significant risk for HIV transmission and acquisition. Entering PSH is a period of transition for homeless persons when integrated care is critically important to ensure positive health outcomes, but these data suggest that PrEP and other HIV prevention services are poorly accessed among this population. As such, multipronged services that integrate PrEP and other HIV prevention services are needed to prevent transmission and acquisition of HIV in this high-risk, vulnerable population and ensure the health and wellbeing of PSH residents.